A Low‐Voltage Layered Na2TiGeO5 Anode for Lithium‐Ion Battery. Issue 14 (19th February 2022) - Liu, Zhiwei; He, Di; Wang, Boya; Wu, Tianhao; Zhao, Shu; Li, Xunlu; He, Shiman; Liang, Yuan; Zhou, Yongning; Sun, Shuhui; Yu, Haijun
Abstract: Titanium‐based anode materials have achieved much progress with the wide studies in lithium‐ion batteries. However, these known materials usually possess high discharge voltage platforms and limited energy densities. Herein, a titanium‐based oxide of Na2 TiGeO5 with layered structure, two‐dimensional lamellar frame and exposed highly active (001) facet, exhibiting good electrochemical performance in terms of high capacity (410 mAh g –1 with a current density of 50 mA g –1 ), excellent rate capability and cycling stability with no obvious capacity attenuation after 4000 cycles, is reported. The appropriate discharge voltage plateau at around 0.2 V endows the Na2 TiGeO5 anode material high security compared with graphite and high energy density compared with spinel Li4 Ti5 O12 . Combining the electrochemical tests and the density functional theory calculations, the Li + storage mechanism of Na2 TiGeO5 is elucidated and the conversion reaction process is revealed. More importantly, this study provides a way to develop low‐voltage and high‐capacity titanium‐based anode materials for efficient energy storage. Abstract : In recent years, titanium‐based anode materials have aroused huge attention due to the safe working potentials and suitable capacities in applications. Herein, a new titanium‐based oxide of Na2 TiGeO5 with the layered structure, two‐dimensional lamellar frame, and the exposed high‐activity (001) facet via the direct hydrothermal method, exhibiting excellent electrochemical performance is designed.